2017
DOI: 10.1002/ecs2.1640
|View full text |Cite
|
Sign up to set email alerts
|

Soil respiration and mass balance estimation of fine root production in Fitzroya cupressoides forests of southern Chile

Abstract: Citation: Urrutia-Jalabert, R., Y. Malhi, and A. Lara. 2017. Soil respiration and mass balance estimation of fine root production in Fitzroya cupressoides forests of southern Chile. Ecosphere 8(4):e01640. 10.1002/ecs2.1640Abstract. The soil carbon dynamics of southern hemisphere temperate rainforests have rarely been studied. Here, we report for the first time soil CO 2 effluxes and their partitioning for medium-age and old-growth Fitzroya cupressoides forests growing under contrasting environmental conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
2
3
0
Order By: Relevance
“…Annual soil respiration measured in our study was higher compared to previous monthly measurements using the manual closed chamber method in Fitzroya forests in 15 points systematically distributed in two 0.6 ha plots located around the tower (637–864 g C m −2 year −1 for years 2011–2012 and 2012–2013, respectively; Urrutia‐Jalabert et al., 2017) although the main drivers (soil temperature and water content) are consistent in both studies. The main difference could be due to the different methods used, since in the previous study, measurements were done using a manual environmental gas analyzer with a closed static chamber once a month (values were interpolated between measurements).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Annual soil respiration measured in our study was higher compared to previous monthly measurements using the manual closed chamber method in Fitzroya forests in 15 points systematically distributed in two 0.6 ha plots located around the tower (637–864 g C m −2 year −1 for years 2011–2012 and 2012–2013, respectively; Urrutia‐Jalabert et al., 2017) although the main drivers (soil temperature and water content) are consistent in both studies. The main difference could be due to the different methods used, since in the previous study, measurements were done using a manual environmental gas analyzer with a closed static chamber once a month (values were interpolated between measurements).…”
Section: Discussionsupporting
confidence: 71%
“…Tree‐ring carbon isotopes showed that despite this declining growth, leaf‐level intrinsic water use efficiency of this forest has increased with rising CO 2 concentrations in the atmosphere, likely due to a decrease in stomatal conductance (Urrutia‐Jalabert, Malhi, Barichivich, et al., 2015). At the ecosystem level, soil respiration in the area was found to increase substantially with warm and dry conditions during summer, reinforcing the idea that the carbon sink of Fitzroya rainforest ecosystems in the Coastal Range can be negatively affected by current and projected climate trends (Urrutia‐Jalabert et al., 2017).…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…For grasslands, we hypothesize that aboveground biomass mortality occurs primarily at the end of the growing season as litterfall (see next section); thus, for the canopy pools E cp = 0.95. In contrast, root mortality depends solely on turnover given that root turnover is still poorly constrained due to the complexity of factors that influence root mortality, the heterogeneity in root life spans, and difficulties in measurement techniques (Urrutia‐Jalabert et al, ; Riley et al, ; Smithwick et al, ). Since root production, respiration, mortality, and turnover all interact, SiB4 uses root respiration efficiencies ( E rp ) ranging from 0.45 to 0.6.…”
Section: Senescencementioning
confidence: 99%